Effects of Primary, Secondary and Tertiary Education on Economic Growth - Loening, Josef L. (World Bank, Washington, DC, 2012)
Loening investigates the impact of human capital on economic growth in Guatemala during 1951-2002 using an error-correction methodology. The results show a better-educated labor force having a positive and significant impact on economic growth. Consistent with microeconomic studies for Guatemala, primary and secondary education are most important for productivity growth. These findings are robust while changing the conditioning set of the variables, controlling for data issues and endogeneity. Due to an environment of social and political conflict, however, total factor productivity has been slightly negative for the past decades, and there is evidence of a missing complementarily between the country's skills and its technology base. The author presents a growth-accounting framework which takes into account quality changes of physical capital, and differentiates by level of education. It shows that the human capital variables explain more than 50 percent of output growth. Of these, secondary schooling is the predominant determinant of growth.